The threshold and spatial effects of PM2.5 pollution on resident health: evidence from China - Song, Yuegang; Xu, Tong (Frontiers in Public Health, 2022)
Based on the general survey of PM2.5 pollution and the number of health insurance buyers at the urban level, this paper establishes a panel threshold model and a spatial econometric model to analyse the impact mechanism and effect of PM2.5 pollution on public health at the urban scale by taking PM2.5 as the representative indicator of air pollution based on the panel data of 256 Chinese cities from 2000 to 2019 in combination with the macroscopic health production function. The research results indicate that higher PM2.5 pollution will significantly increase the health insurance buyers in China; if the threshold effect is taken into consideration, the per capita GDP has a nonlinear relationship with the increasing marginal effect on the higher number of health insurance buyers; because of the spatial spillover effects, the PM2.5 pollution brings more impact on the number of health insurance buyers , it indicates that the ignorance of the spatial correlation will cause underestimation of the impact of PM2.5 pollution on resident health. The robustness of the adjacency matrix and the geographic distance matrix shows that the regression results in this paper are of robustness and reliability.